Penerapan Knowledge Management dalam Layanan Pelatihan Kerajinan: Studi Kuantitatif di BBSPJIKB Yogyakarta - Paramadharma, Harnandito; Kirana, Kusuma Chandra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Craft is an industry based on culture and local wisdom. The ability or skill of a person in making crafts is obtained through life experience and the influence of local culture so that it forms as tacit knowledge. In knowledge management, the SECI model is applied in an organization to encourage innovation and accelerate knowledge transfer. The purpose of this study is to photograph the phenomenon of the application of knowledge management in the BBSPJIKB craft team. The method used in this study is quantitative descriptive, through a knowledge management questionnaire in the Master of Management program lecture module at Sarjanawiyata Tamansiswa University Yogyakarta, which was tested for validity and reliability. The results showed that the results of the questionnaire study were quite valid with only 1 invalid question out of a total of 16 questions. From the results of the reliability test, it can be concluded that the questionnaire instrument is very reliable because the alpha value is 0.95, far above the minimum standard of 0.7. All questions have good internal consistency. So this questionnaire can be trusted and relied on for decision making or further research. The results of the study concluded that the implementation of knowledge management in the BBSPJIKB Craft Team was quite good, especially in terms of the culture of sharing and active learning. However, the empowerment of digital platforms and reward programs for innovation need to be improved.